Symbolic forms and cognition - Hong Liu, Chang; Kennedy, John M. (Psyke & Logos, 2023)
Two shapes - a cire le and a square - are used to study the effects of form symbolism in cognitive tasks. The first experiment examines the degree of consensus between subjects matching a list of pairs of words with the pair of shapes. The second experiment examines the correlation between the degree of consensus and the reaction times required in the matching task. The third experiment examines the effect of the consensus on performance on a recall task. The findings indicate there is significant consensus between subjects in tasks assessing form symbolism, the amount of consensus predicts reaction time on the matching task and the amount of consensus also predicts performance on the memory task.